(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
For long periods, schools of memorizing the Holy Qur’an in Algerian society played the basic role in education and value acquisition as well as building the national personality and preserving local constants. In a continuous tragic process, these schools were able to lead the hierarchy of institutions of socialization in the national collective imagination that lead it to be the first and preferred destination for the Algerian family towards the value and ethical’s acquisition and guidance of its children. The sociological context to understand the current functional role played by Qur’anic schools in Algeria requires tracking these institutions by studying and analyzing in stages through historical periods and trying to present them to discourses and sayings of socialization, as the socio-historical narrative of them enables us to visualize the limits of the relationship between these schools and the components of the Algerian national personality. Research paperwork is an empirical study that has chosen the Qur’anic schools of the Algerian Association of Guidance and Reform as a sample of study, trying to research dimensions and indicators of the relationship between these Qur’anic schools and the national personality by addressing the local values and constants that they gain for their members as intermediate variables with deep and manifest sociological connotations.